The Role of Parents in Guiding Children to Dress as Muslim Women - Nasution, Marwiyah; Siregar, Dame; Lubis, Sufrin Efendi (Fahmina: Jurnal Pendidikan Islam, 2025)
This research is based on the lack of awareness and interest of children in Muslim women's clothing. With that, the encouragement of parents is very influential to guide their children to always be used to always wearing Muslim clothes. The formulation of this research problem is how is the model of children's Muslim women's clothing in the Sungai Dua Environment, Langga Payung Village, Sungai Kanan District, South Labuhanbatu Regency?, what is the role of parents in guiding children to dress in musliimah in the Sungai Dua Environment, Langga Payung Village, Sungai Kanan District, South Labuhanbatu Regency?. The method used in this study is qualitative research because of its descriptive analysis nature with a case study approach. The data sources are parents and children, data collection techniques used for observation, and interviews. Meanwhile, data processing and data analysis by reducing data, presenting data, and then concluding data. Furthermore, data analysis, checking the validity of the data using the triangulation method. The results of this study can be concluded that the application of the model of children's Muslim women's clothing in the Sungai Dua Environment has met the Islamic law, but it is necessary to always control the children so that they always wear Muslim women's clothing until adulthood. both in activities around the house and activities outside the home. This is in accordance with the results of observations made by the researcher that the ethics of wearing Muslim women's clothing in the Sungai Dua Environment have met.